Hypoxia and lineage specification of cell line-derived colorectal cancer stem cells. - Yeung, T; Gandhi, S; Bodmer, W (2011)
Hypoxia is an important regulator of normal and cancer stem cell (CSC) differentiation. Colorectal CSCs from SW1222, LS180, and CCK81 colorectal cancer-derived cell lines are able to differentiate into complex 3D lumen-containing structures in normoxia, whereas in hypoxia, they form undifferentiated dense colonies that have reduced expression of the enterocyte differentiation marker CDX1, lack goblet cell formation, and have increased expression of BMI1 and activated Notch1. Hypoxia increases the clonogenicity of CSCs, which is cumulative as each round of hypoxia enriches for more CSCs. The hypoxic phenotype is reversible, because cells from hypoxic-dense colonies are able to reform differentiated structures when regrown in normoxia. We show that CDX1 is able to stimulate the generation of lumens even in hypoxia and has a negative feedback on BMI1 expression. Knockdown of CDX1 reduces lumen formation but does not affect goblet cell formation, suggesting that enterocytes and goblet cells form from different progenitor cells. Notch inhibition by dibenzazepine (DBZ) allowed CSCs to form goblet cells in both normoxia and hypoxia. Finally, we show that Hif1α, but not CA9, is an important mediator of the effects of hypoxia on the clonogenicity and differentiation of CSCs. In summary, hypoxia maintains the stem-like phenotype of colorectal cell line-derived CSCs and prevents differentiation of enterocytes and goblet cells by regulating CDX1 and Notch1, suggesting that this regulation is an important component of how hypoxia controls the switch between stemness and differentiation in CSCs.